The Relationship Between Floods and Dengue Fever Incidence: Epidemiology, Risk Factors, and Prevention: A Literature Review - Valizha Putri (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
In recent years, climate change has led to increased rainfall resulting in flooding, which has a close relationship with a rise in dengue fever (DBD) cases as it creates an ideal environment for the Aedes aegypti mosquito, the main vector of the disease. Dengue fever is one of the major health problems in tropical countries such as Indonesia, which has the highest number of cases in Southeast Asia. The method used in this literature review was to determine the topic, then identify keywords to search for journals in English using databases including Google Scholar, ScienceDirect, PubMed, and SINTA. This review analyzes the relationship between flooding and the incidence of dengue fever, and discusses epidemiology, risk factors, and prevention, as flooding is a frequent natural disaster in Indonesia. The conclusion is that there is a relationship between flooding and dengue fever, because floods create puddles of water that can serve as breeding grounds for Aedes aegypti. Dengue fever is endemic in more than 100 countries, especially in tropical and subtropical regions. Various risk factors can exacerbate its incidence, including environmental, socioeconomic, and behavioral factors. Dengue can be prevented in multiple ways, one of which is implementing the 3M Plus Mosquito Nest Eradication (PSN) program: draining water reservoirs, closing containers that can hold water, and reusing used goods that have the potential to become mosquito nests. These measures need to be implemented to reduce dengue fever cases.